Emancipatory Of Legal Transendency In Indonesia: Study Of Moral Aspects In The Making Of Laws And Regulations In Indonesia - Triwahyuningsih Triwahyuningsih (Journal of Transcendental Law, 2019)
ABSTRACT Objectives: This paper aims to answer the question of how the relationship between law and moralism, as well as how to internalize moral principles in making laws and regulations in Indonesia. Methodology: This study used a philosophical approach that aimed to explore the relationship between law and morals from the perspective of John Austin, Kelsen, and H. L. A Hart. It also used the transcendental perspectives in exploring the importance of internalizing moral principles in making laws and regulations in Indonesia. The research method in the article used descriptive normative research methods, with interpretative data processing techniques regarding the importance of moral aspects in making laws and regulations in Indonesia. Findings: The dominance of the philosophy of positivism has broad implications. The closure of the law to morality raised by adherents of legalism, legal positivism, or reinerechtslehre does not only raise injustice everywhere but also appear with a face of totalitarian or repressive law. Law and moral relations, according to John Austin (1790-1859), are diametrically separated and tend to favor the law (the law negates morals), while Hans Kelsen and Austin place religious and moral inferiority while favoring positive law. According to Kelsen, the law deals with the form (formal), not the content (material); then, Hart tries to offer the principle of morality as a minimum legal requirement in which the pattern of the relationship is cooperative or independent dialogue. Whereas in the transcendent perspective, law and morals are in a dialogue-integrative relationship. The legislators should have spiritual intelligence; that is, they do not want to be bound and limited by existing standards but want to go beyond and transcend the existing situations (transcendental).  With spirituality, the legislators, who are in accordance with the principle, can produce laws that show the emancipatory of legal transcendency. The laws do not only humanize humans but are also oriented to moral values that originate from God. Benefit: The benefit of this paper is to be the basis for guarding moral values in making the Law, starting from the preparation and initiative for the submission of the draft law, discussion of the draft law, and approval of the draft law. Originality/novelty: Internalization of moral principles in law can produce laws that can make people happy and answer the problems of human life. At least three elements are fulfilled, namely justice, efficacy, and legal certainty. Keywords: transcendency, morals, the formation of laws